2018
DOI: 10.1096/fj.201701256rrr
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐dependent, dual roles of IL‐10 in the osteogenesis of human BMSCsviaP38/MAPK and NF‐κB signaling pathways

Abstract: Microenvironmental conditions can influence the differentiation and functional roles of mesenchymal stem cells (MSCs). Recent studies have suggested that an inflammatory microenvironment can significantly affect the osteogenic differentiation of MSCs. Here, we show, for the first time, that IL-10 has concentration-dependent, dual roles in the osteogenesis of human bone marrow mesenchymal stem cells (hBMSCs). Low physiologic concentrations of IL-10 (0.01-1.0 ng/ml) activate the p38/MAPK signaling pathway to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 59 publications
(70 reference statements)
5
49
0
Order By: Relevance
“…Phenotypic switching of macrophages during fracture repair leads to the production of IL-10, found in serum samples from fracture hematomas of patients at concentrations around 1 ng/ml [36]. A recent study showed that recombinant IL-10 can enhance MSC osteogenesis via the p38/mitogen-activated protein kinase (MAPK) signaling pathway [25]. To our knowledge, our study is the first to demonstrate that IL-10 secreted by macrophages regulates MSC osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Phenotypic switching of macrophages during fracture repair leads to the production of IL-10, found in serum samples from fracture hematomas of patients at concentrations around 1 ng/ml [36]. A recent study showed that recombinant IL-10 can enhance MSC osteogenesis via the p38/mitogen-activated protein kinase (MAPK) signaling pathway [25]. To our knowledge, our study is the first to demonstrate that IL-10 secreted by macrophages regulates MSC osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 59%
“…We recently reported that IL-10 originated from pro-resolving macrophages enhances MSC immunomodulatory potential in vitro [18]. In addition, a recent study showed that physiological doses of recombinant IL-10 stimulate MSC osteogenic differentiation while higher pathological doses inhibit it [25].…”
Section: Introductionmentioning
confidence: 99%
“…As a key anti-inflammatory cytokine, IL-10 participates in immune response and regulates by multiple signaling pathways in the activated macrophages [29][30][31]. Previous studies have shown that PCV2 infection activates the PI3K/Akt pathway to suppress premature apoptosis for improved virus growth and aggravate the effects on autophagy and PCV2 replication [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…AGN194310 might regulate chondrocyte proliferation and differentiation to maintain endochondral ossification through accession of NF-κB and reduction of p38 MAPK signaling pathway [34]. However, the mechanisms of crosstalk between p38 MAPK and NF-kB signaling are not fully clarified [35], and require further investigation of AGN194310 effects on NF-kB signaling in future studies.…”
Section: Discussionmentioning
confidence: 99%